2019
DOI: 10.2174/1568026619666190308131805
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Immuno-Oncology Therapy: Advances, Challenges and New Directions

Abstract: Oncology immunotherapy has gained significant advances in recent years and benefits cancer patients with superior efficacy and superior clinical responses. Currently over ten immune checkpoint antibodies targeting CTLA-4 and PD-1/PD-L1 have received regulatory approval worldwide and over thousands are under active clinical trials. However, compared to the rapid advance of Monoclonal Antibody (mAb), studies on immunotherapeutic small molecules have far lagged behind. Small molecule immunotherapy not only can ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…18,19 Some IDO1 inhibitors have been developed and applied in antitumor therapy in preclinical and clinical trials. 50 Although IDO1 inhibitors have not demonstrated antitumor activity as single agents in orthotopic glioma animals, a unique synergy when combined with radiotherapy, temozolomide, or anti-programmed cell death protein 1 antibody has been noted. [28][29][30][51][52][53] TDO inhibitors have not been tested in glioma animals.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Some IDO1 inhibitors have been developed and applied in antitumor therapy in preclinical and clinical trials. 50 Although IDO1 inhibitors have not demonstrated antitumor activity as single agents in orthotopic glioma animals, a unique synergy when combined with radiotherapy, temozolomide, or anti-programmed cell death protein 1 antibody has been noted. [28][29][30][51][52][53] TDO inhibitors have not been tested in glioma animals.…”
Section: Discussionmentioning
confidence: 99%
“…All these IDO1 inhibitors were shown to be safe and well-tolerated (158)(159)(160)(161). Epacadostat is the clinically most advanced IDO1 inhibitor and has been shown to inhibit tumor growth in mice models (162).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…Unfortunately, a recent trial with combined administration of epacadostat with pembrolizumab found no superiority over pembrolizumab alone (169). Despite this setback, several ongoing trials investigate the effect of other (also structurally new) IDO1 inhibitors in combination with different immunotherapies (162).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…Enhancement of the anti-tumor response of neutrophils can also be achieved by targeting signaling partners downstream of the inhibitory receptors. Even better, combination of ligand-receptor interaction disruption and simultaneous blockade of a protein functioning downstream, could have a substantial impact ( 234 , 235 ). Protein tyrosine kinases (PTKs) and protein tyrosine phosphatases (PTPs) are two important regulators of immune cell responses.…”
Section: Targeting Neutrophil Activity In Cancer Therapymentioning
confidence: 99%